Predicting past, current and future habitat suitability and geographic distribution of the Iranian endemic species Microgecko latifi (Sauria: Gekkonidae). (December 2020) - Hosseinzadeh, Mahboubeh Sadat; Fois, Mauro; Zangi, Bahman; Kazemi, Seyed Mahdi
Abstract: The genus Microgecko Nikolsky 1907 belongs to the family Gekkonidae and contains eight species distributed in Iran, Pakistan, Afghanistan, northwestern India and, probably, in Iraq. Among them, the Latifi's dwarf gecko, Microgecko latifi, is endemic to central and southwestern Iran. We used MaxEnt modeling approach to investigate the effects of climate change and potential distribution of M. latifi . A total of 29 presence records and five factors related to precipitation and temperature were collected and used in the modeling approach for past, present and future. Our findings showed that Central Persia, the largest terrestrial ecoregion of Iran, hosts the most suitable environment for M. latifi under the current climate as well as under future scenarios. Differently, Zagros Mountains hosted the most suitable environment for this species under past climate. This is in line with previous studies that identified Zagros, Alborz, Kopet-Dagh Mountains and northwestern Iran as important Pleistocene refugia. Among environmental variables, precipitation of the warmest quarter was the most important driving factor for all models. According to other studies, species richness and diversity of lizards in Iran are higher in hot and arid environments; also considering the possible effects of global warming, further investigations are required in those environments. Highlights: Microgecko latifi, a gecko endemic to central and southwestern Iran. MaxEnt was used to investigate the effect of climate on the distribution of M. latifi . Species richness and diversity of lizards in Iran are higher in arid environments. Central Persia is the most current and future suitable environment for M. latifi . Zagros Mountains were confirmed as an important Pleistocene refugium.